2014
DOI: 10.1371/journal.pone.0115018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-Angiogenesis on Glioblastoma Growth and Migration: Model to Clinical Predictions

Abstract: Glioblastoma multiforme (GBM) causes significant neurological morbidity and short survival times. Brain invasion by GBM is associated with poor prognosis. Recent clinical trials of bevacizumab in newly-diagnosed GBM found no beneficial effects on overall survival times; however, the baseline health-related quality of life and performance status were maintained longer in the bevacizumab group and the glucocorticoid requirement was lower. Here, we construct a clinical-scale model of GBM whose predictions uncover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…All the three more complete GBM models mentioned in the text [47, 48, 51] predict that in the evolution of the disease, the biologically active region (proliferating and infiltrating) is pushed toward the periphery of the tumor, while the central part becomes progressively larger and necrotic. Therefore, it seems reasonable to concentrate in this peripheral region both radiation and HT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the three more complete GBM models mentioned in the text [47, 48, 51] predict that in the evolution of the disease, the biologically active region (proliferating and infiltrating) is pushed toward the periphery of the tumor, while the central part becomes progressively larger and necrotic. Therefore, it seems reasonable to concentrate in this peripheral region both radiation and HT.…”
Section: Discussionmentioning
confidence: 99%
“…To solve this gap, more detailed models, with five or more equations describing the main tumor elements (such as normal, necrotic and hypoxic tumor cells, vascularity, nutrients, etc.) were subsequently proposed [4551]. …”
Section: Methodsmentioning
confidence: 99%
“…The authors have recently reported a system of partial differential equations (PDE) that models GBM at the scale of MRI; the equations model replication, brain invasion, angiogenesis, and hypoxia [4, 5]. Here, we modify the system of equations to eliminate the GoG phenotype, thus reducing the system to a single glioma cell model; the equations are shown in Table 1, and the parameter values and units are displayed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…necrosis, enhancing ring and edema, but also reproduces specific tumor progression patterns and their associated average patient survival times [4, 5]. This model incorporates the GoG phenotype by including two specific cell types, Invasive (I) cells and Proliferative (P) cells, which can switch back and forth between one phenotype or another depending on the nutrient environment in the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation